A comparative multi‐reference configuration interaction study of the low‐lying states of two thione isomers of thiophenol - Lima, Filipe Belarmino de (2020)
Multi-reference configuration interaction, MR-CI (including extensivity corrections, named +Q) calculations have been performed on S0 to S3 states of cyclohexa-2,4- diene-1-thione (thione 24) and cyclohexa-2,5-diene-1-thione (thione 25), which are thione isomers of thiophenol. Several types of uncontracted MR-CIS and MR-CISD wavefunctions have been employed, comprising MR-CI expansions as large as ~ 365 x 106 configuration state functions. The nature of the studied excited states has been characterized. Vertical excitation energies (E) and oscillator strengths (f) have been computed. The most intense transitions (S0→S2 for 24 and S0→S3 for 25) do not change with the wavefunction, although a variation as large as ~ 1 eV has been obtained for the S3 state of 24, at the highest (MR-CI+Q) level. On the other hand, E changes at most ~ 0.56 eV for 25, as the wavefunction changes, at the same level. The S1 state of both thiones has nπ* character and is in the visible region. For 24 S2 and S3 are ππ* and nπ* states, respectively, while for 25 the reverse order has been obtained. S2 and S3 are in the range from ~ 3.5 to 5.2 eV, again at the highest level. It is the first time that the excited states of the title molecules are studied. The computed results agree with the experimental onsets of photoreactions of thiones 24 and 25 found by Reva et. al. (Phys. Chem. Chem. Phys. 2015, 17, 4888).